Comparison of the Effectiveness of Calcined Chicken and Duck Eggshells as Zn Metal Adsorbent Using Atomic Absorption Spectrophotometric - Hanifah, Hesty Nuur; Hadisoebroto, Ginayanti; Cunayah, Cucun; Dani, Diyanti Alma Kusuma (Universitas Gadjah Mada, 2024)
Zinc is a heavy metal that is often found in liquid waste and causes water pollution. Eggshells can be used as an adsorbent to reduce heavy metals in water because they have a lot of pores, CaCO3, and mucopolysaccharide acid protein. This study aimed to determine the effectiveness of a comparison between calcined chicken and duck eggshells to adsorb Zn, by determining the optimum pH, contact time, optimum mass, and the characterization of adsorbents. The results of this study showed that calcined chicken eggshells adsorb Zn at an optimum pH of 6, with the required optimum contact of 75 min and a mass of 400 mg with adsorption effectiveness of 99.64%. Meanwhile, calcined duck eggshells have an optimum pH of 6, an optimum contact time of 60 min, and an optimum mass of 400 mg with adsorption effectiveness of 99.73%. Activated carbon from the market has an adsorption effectiveness of 99.53%. So, it can be concluded that calcined chicken and duck eggshells can be used as zinc metal adsorbent.